2018
DOI: 10.1001/jamaoncol.2017.5082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Treatment With Tumor-Treating Fields on Health-Related Quality of Life of Patients With Newly Diagnosed Glioblastoma

Abstract: clinicaltrials.gov Identifier: NCT00916409.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(131 citation statements)
references
References 32 publications
4
113
0
Order By: Relevance
“…The 5-year survival rate for patients in the TTFields plus TMZ group was 13% (vs. 5% for TMZ alone; P < 0.001), and the 2-year survival rate was 43% (vs. 31% for TMZ alone; P < 0.001) (4). Healthrelated quality of life was not compromised by the addition of TTFields (5).…”
Section: Introductionmentioning
confidence: 97%
“…The 5-year survival rate for patients in the TTFields plus TMZ group was 13% (vs. 5% for TMZ alone; P < 0.001), and the 2-year survival rate was 43% (vs. 31% for TMZ alone; P < 0.001) (4). Healthrelated quality of life was not compromised by the addition of TTFields (5).…”
Section: Introductionmentioning
confidence: 97%
“…Mild to moderate scalp toxicity underneath the transducer arrays was seen in 52% of patients who received TTFields and temozolomide compared to none in the control cohort. Systemic toxicities and health-related quality-of-life measures were comparable between the two groups [2,17].…”
Section: Clinical Outcome From Ttfields Treatmentmentioning
confidence: 87%
“…However, after a median follow-up of 40 months, a significant median survival benefit of 4.9 months was evident (20.9 vs. 16.0 months) [27]. The health-related quality of life was equal in both arms of the trial [28]. Secondly, the results from the German CeTeG-Trial have been reported at the SNO conference in 2017.…”
Section: Glioblastomamentioning
confidence: 98%